Adhesive joints between carbon fiber and aluminum foam reinforced by surface‐treated aramid fibers. Issue 1 (12th February 2014) - Sun, Zhi; Shi, Shanshan; Hu, Xiaozhi; Chen, Haoran; Wong, Zachary
<x xml:space="preserve">Abstract</x> Short aramid fibers have been successfully used to reinforce the interface adhesive property between carbon fiber/epoxy composites and aluminum foam, and to form aramid‐fiber "composite adhesive joints." In this study, to further improve the reinforcing effect of the aramid‐fiber‐reinforced adhesive joints, aramid fibers were ultrasonic treated to conduct different surface conditions. Critical energy release rate of the carbon fiber/aluminum foam sandwich beams with as‐received and treated interfacial aramid fibers were measured to study the influence of the surface treatment on aramid fibers. It was found that reinforcements in critical energy release rate were achieved for all samples with treated aramid fiber as measured under double cantilever beam condition. The interfacial characteristics of the short aramid fibers with different surface condition were investigated and discussed based on scanning electron microscopy observations. It is suggested that advanced bonding between aramid fibers and epoxy resin was conducted after surface treatment, and more energy was therefore absorbed through fiber bridging during crack opening and extension process. POLYM. COMPOS., 36:192–197, 2015. © 2014 Society of Plastics Engineers